Protein lactylation in kidney diseases - Yelei Xu; Xinming Li; Xinming Li; Zhiguo Mao; Cheng Xue (Frontiers in Cell and Developmental Biology)
Post-translational modifications (PTMs) regulate protein function and structure through covalent modifications, participating in various physiological and pathological processes. Lysine lactylation is an emerging PTM discovered in recent years, which regulates gene expression, metabolism, and cell signaling by adding a lactyl group to lysine residues. As a by-product of glycolysis, lactate not only influences cellular metabolism but also contributes to the development and progression of kidney diseases through lactylation. This review focuses on the discovery and regulatory mechanisms of lysine lactylation, particularly its role in kidney diseases such as acute kidney injury, chronic kidney disease, and diabetic kidney disease. Lactylation influences the metabolic state, inflammatory response, and fibrosis of renal cells by modulating protein function and key gene transcription. With continued research, lactylation is expected to become a novel target for understanding the metabolic-epigenetic regulation of kidney diseases and could offer new strategies for treatment.